Akar Benih Krisis Indonesia: Suatu Tinjauan Sejarah dan Tinjauan Asumsi-asumsi Pembangunan - W. J. Wawaroentoe (Journal of Regional and City Planning, 1998)
I do not believe that civilizations are fated to break down, so I begin by exposing the fallacious arguments of the determinists. Having rejected determinist explanations, I look for an alternative. I find that the very process by which growth is sustained is inherently risky: the creative leadership of a society has to resort to social 'drill' in order to carry along the uncreative mass, and this mechanical device turns against its masters when their creative inspiration fails. I then have to account for the failure of creativity, and I ascribe it to the spiritual demoralization to which we human beings seems to be prone on the morrow of great achievements "” a demoralization to which we are not bound to succumb and for which we ourselves therefore bear the responsibility. Success seems to make us lazy or self satisfied or conceited, J muster a series of notable historical examples to show how this actually happens and how human beings have erred in each case. (dikutip dari: Why have some civilizations broken down in the past? Dalam buku A Study of History karangan Arnold Toynbee, 1972: Oxford University Press and Thames and Hudson Ltd. Dengan catatan kata-kata yang telah dipertebal telah dipilib oleh pengutip)